CONSTITUTIONAL BASIS OF THE CONCEPT OF INADMISSIBILITY OF EVIDENCE IN UKRANIAN CRIMINAL PROCEEDINGS (Bulletin of criminological association of Ukraine, 2025)
The constitutional basis of the concept of inadmissibility of evidence in criminal proceedings has been investigated. It has been established that the rule on the inadmissibility of evidence in criminal proceedings should be considered as a guarantee against groundless and unfounded accusation, which has constitutional roots and is a component of the principle of the presumption of innocence and the right to a fair trial. It is noted that the legislator's approach, applied in Part 1 of Article 87 of the Code of Criminal Procedure of Ukraine to divide violations of human rights and freedoms into essential and non-essential, is unconstitutional, as it leads to a violation of the constitutional obligation of the state to guarantee constitutional rights and freedoms, which is defined in Part 2 of Article 22 of the Constitution of Ukraine. When determining the grounds for recognizing evidence as inadmissible, the concepts of violation of human rights and freedoms and their restrictions should be distinguished. Restriction of human rights and freedoms consists in the legislative narrowing of their content and scope, which is carried out for the purpose of due recognition and respect for the rights and freedoms of others and ensuring the fair requirements of morality, public order and general well-being in a democratic society. When as a violation of rights and freedoms is an activity that consists in non-compliance with legally defined human rights and freedoms and mechanisms for their restriction.
Keywords: criminal proceedings; evidence and proving; inadmissibility of evidence; presumption of innocence; right to a fair trial